Effect of Rosmarinus Officinalis Essential Oil On Anxiety, Depression, And Sleep Quality - Alvarado-García, Paul Alan Arkin (2023)
Introduction: The objective of this investigation was to evaluate the effect of Rosmarinus officinalis essential oil on anxiety, depression, and sleep quality. Methods: The essential oils were extracted by hydro-distillation using a modified Clevenger-type apparatus and the chemical composition was performed by Gas chromatography with flame ionization detection (GC-FID) and Gas chromatography mass spectrometry (GC–MS). Furthermore, a quasi-experimental study was conducted, where 81 participants were divided into two groups, comprising a waiting list control group and an experimental group treated with essential oils. Anxiety and depression indexes were evaluated using the Zung Self-Rating Anxiety Scale (SAS) and the Zung Self-Rating Depression Scale (SDS), and sleep quality was measured with the Pittsburgh Sleep Quality Inventory (PSQI). Results: Chemical analysis showed that 1,8 cineole (37.6%), α-pinene (19.9%), and linalool (15.8%) were the main components. Anxiety, depression, and sleep quality scores showed a decrease in the post-test study phase compared to the pre-test in the experimental group (p<0.05). A large size effect was found in the case of anxiety (d = 1.491; g= 1.490) with 1-β=0.996, while medium size effects were observed for depression (d = 0.581; g= 0.582) with 1-β=0.585; and sleep quality (d = 0.586; g = 0.588) with 1-β=0.638. Conclusion: Essential oils extracted from Rosmarinus officinalis are more effective in calming anxiety and show moderate changes in depression and sleep quality.